PROPUESTA METODOLÓGICA DE INCLUSIÓN, DESDE LA EDUCACIÓN FISICA (Fiep Bulletin - online, 2019)
To specify the term to integrate and overvalue inclusion, which benefits the students / users within the society, tocontribute their talents and be reciprocated with the benefits offered, avoiding discrimination and seeking inclusion, not in an actof solidarity with those who might be considered relegated from society, but with a possibility of improvement for all. Incidentally,we propose an inclusive education (UNESCO): a process to identify and respond to the diversity of students' needs, throughgreater participation in learning, cultures and communities, and reducing exclusion in education. Education, facilitatingsuccessful learning for all children, reducing all types of exclusion from a human rights perspective to an education with accessand successful participation with a quality education for all.
Keywords: Integration; Inclusion; Inclusive school; Disability; Education right